2013
DOI: 10.1007/978-1-4614-6217-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Skin for Microneedle Delivery of Influenza Vaccine

Abstract: Influenza infection represents a major socioeconomic burden worldwide. Skin represents a new target that has gained much attention in recent years for delivery of influenza vaccine as an alternative to the conventional intramuscular route of immunization. In this review we describe different microneedle vaccination approaches used in vivo, including metal and dissolving microneedle patches that have demonstrated promising results. Additionally we analyze the immunological basis for microneedle skin immunizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 132 publications
0
31
0
Order By: Relevance
“…However, migration of cells can occur, initiated by the release of molecules, such as cytokines and chemokines, from skin cells (Ueno et al 2007;Koutsonanos et al 2013). These molecules provide a signal to cells from both inside and outside the skin to migrate towards the location of secretion (Del Pilar Martin et al 2012;Koutsonanos et al 2013) and thereby repopulating the skin and changing the number and distribution of cells within the skin. In addition, these signaling molecules can influence the maturation and migration of antigen presenting cells towards the lymph nodes (Koutsonanos et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, migration of cells can occur, initiated by the release of molecules, such as cytokines and chemokines, from skin cells (Ueno et al 2007;Koutsonanos et al 2013). These molecules provide a signal to cells from both inside and outside the skin to migrate towards the location of secretion (Del Pilar Martin et al 2012;Koutsonanos et al 2013) and thereby repopulating the skin and changing the number and distribution of cells within the skin. In addition, these signaling molecules can influence the maturation and migration of antigen presenting cells towards the lymph nodes (Koutsonanos et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules provide a signal to cells from both inside and outside the skin to migrate towards the location of secretion (Del Pilar Martin et al 2012;Koutsonanos et al 2013) and thereby repopulating the skin and changing the number and distribution of cells within the skin. In addition, these signaling molecules can influence the maturation and migration of antigen presenting cells towards the lymph nodes (Koutsonanos et al 2013). If these processes were included in the model, the release rate may prove to influence the evoked immune response when a sustained period is simulated, since it has been reported that a vaccination regime over many days can increase the response (Johansen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One such example for vaccines delivery is reported by Edmonston-Zagreb for measles vaccination (Nordquist et al, 2007;Herwadkar & Banga, 2012;Kis et al, 2012;Singh et al, 2012;Edens et al, 2013;Koutsonanos et al, 2013;Ling & Chen, 2013;Cai et al, 2014;Gill et al, 2014). Vaccinations have the capacity to be delivered using MN patches, which require the patient to have no specialized training or the need for cold/refrigerated storage; this in turn can reduce the spread of diseases Edens et al, 2013).…”
Section: Why Mns?mentioning
confidence: 99%
“…When an antigen is delivered in the epidermis and dermis, it will diffuse through the different skin layers (Raphael et al, 2013;Römgens et al, 2015). One of these layers, the viable epidermis, is mainly composed of keratinocytes, but also contains a large population of Langerhans cells (Koutsonanos et al, 2013). Beneath the epidermis lies the dermis, a relatively thick layer rich in collagen fibres.…”
Section: Introductionmentioning
confidence: 99%
“…They can be recognized, bind and be internalized by the cells residing in the skin (Giese, 2013;Koutsonanos et al, 2013). This uptake of antigens occurs by receptor-mediated endocytosis or by fluid phase pinocytosis (Abbas et al, 2012;Mizuno et al, 2004).…”
Section: Introductionmentioning
confidence: 99%